Curcumin encapsulated chitosan nanoparticles as antiviral therapy against feline infectious peritonitis - Ng, Shing Wei (2018)
Feline infectious peritonitis (FIP) is a fatal immune-mediated disease caused by coronavirus known as feline infectious peritonitis virus (FIPV). The occurrence of FIP is greatly affecting cat populations worldwide especially kittens and immunocompromised cats. To date, there is no effective vaccine or antiviral treatment against this deadly disease. Curcumin is a natural polyphenol compound extracted from Curcuma longa, which is renowned for its wide spectrum of biological and pharmacological activities in profound diseases and disorders. However, poor bioavailability of curcumin has limited its own potential as an effective therapeutic agent. The oral bioavailability can be enhanced with polymeric nanoparticles as a delivery system for curcumin. The main objective of this study was to evaluate the therapeutic effects of synthesized chitosan-based curcumin nanoparticles for FIP in vitro and in vivo. Curcumin encapsulated chitosan (Cur-CS) nanoparticles were prepared via ionic-gelation method and the physicochemical properties of nanoparticles were characterized. The Cur-CS nanoparticles were found in size approximately 330 nm with positive surface charges of 42.1 ± 3.0 mV. A sustained release of curcumin for 24 hours was observed. Moreover, enhanced cellular uptake of curcumin was observed in cells treated with Cur-CS nanoparticles compared to curcumin. The nanoparticles were stored at 4ºC for up to one month without changes in physical properties. The cell cytotoxicity, antiviral and anti-inflammatory activities of curcumin and Cur-CS nanoparticles were evaluated in Crandell Reese feline kidney (CrFK) cells. Cur-CS nanoparticles showed reduced cytotoxicity compared to curcumin. The viral inhibitory effects of Cur-CS nanoparticles were significantly greater than curcumin in FIPV-infected cells where increased cellular protection percentage in co-inoculation treatment and significant reduction in viral copy number were detected. Cur-CS nanoparticles also exhibited enhanced anti-inflammatory activities compared to curcumin in virus-infected cells. Pharmacokinetic study and clinicopathologic evaluation of curcumin and Cur-CS nanoparticles were determined in clinically healthy cats. The oral bioavailability of curcumin was improved when delivered via chitosan nanoparticles where higher plasma curcumin concentrations were noted in cats administered with Cur-CS nanoparticles, with a relative bioavailability of 301% compared to curcumin. Furthermore, the clinicopathologic evaluation results indicated no significant toxicological effect in body weights, urinalysis, haematology and serum biochemistry parameters in cats administered with 100 mg/kg of chitosan nanoparticles, 100 mg/kg of curcumin and 100 mg/kg of Cur- CS nanoparticles, either once daily or twice daily, for 28 days. The antiviral and antiinflammatory effects of Cur-CS nanoparticles were further evaluated in FIP diagnosed cats. A total of 22 cats that fulfilled the criteria were recruited, however, only nine cats were sustained for data analysis. Out of the nine cats, two cats were successfully completed the 28 days clinical study and returned to the owners. The efficacy of Cur- CS nanoparticles was studied upon comparison among before and after treatments. The viral inhibitory effect of Cur-CS nanoparticle was evidenced by the reduced viral titre in macrophages in ascites. In addition, combination treatment of prednisolone and Cur-CS nanoparticles showed enhanced anti-inflammatory effects in FIP diagnosed cats compared to prednisolone and Cur-CS nanoparticles alone. However, the results also showed there were no significant effects of Cur-CS nanoparticles on survival time, the quality of life or any clinical or laboratory parameter in cats diagnosed with FIP. In conclusion, Cur-CS nanoparticles showed antiviral and anti-inflammatory effects in FIPV infection and further investigation will be necessary to scrutinize the possibility of a combination of curcumin and other agents as an effective FIP treatment.